Qualitative Analysis of Borax in Wet Noodles in Makassar City - Sari, Nur Indah; Ahmad, Fandi; Amaliah, Rezeki (Hayyan Journal, 2024)
Borax, or sodium tetraborate, is a dangerous chemical compound that is banned from use as a preservative in food due to its potential health risks. Wet or instant noodles are a form of processed food from wheat flour that is widely consumed and favored by various levels of society, especially in school. The addition of borax to wet noodles aims to increase the chewiness and shelf life of the noodles. This study aims to identify the presence of borax in school's snack noodles. Qualitative analysis was used as the research method with purposive sampling technique in three sub-districts, namely Tamalate, Mamajang, and Rappocini sub-districts of Makassar City. The sampling criteria were wet noodles complementing meatball snacks from street vendors in front of the gate of elementary schools, and 15 noodle samples were obtained. Qualitative analysis was carried out by organoleptic test and color change of filter paper that had been soaked in curcumin extract from turmeric. The results showed that the wet noodle samples were pale yellow to bright yellow in color with a maximum shelf life of 24 hours. The test results with turmenic paper showed no color change, so it was concluded that all noodle samples did not contain borax.